Retrospective Analysis of Viral Hepatitis B Incidence in Russia from 2013 to 2017 in the Context of Preventive Vaccination - L. M. Khantimirova; T. Yu. Kozlova; E. L. Postnova; V. A. Shevtsov; A. V. Rukavishnikov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article presents the results of a retrospective analysis of viral hepatitis B incidence in the Russian Federation from 2013 to 2017, taking into account the use of vaccines included into the National Immunisation Schedule and the Immunisation Programme in Case of Epidemic Outbreaks. The analysis of the data revealed a trend towards a reduction in the incidence of acute and chronic forms of hepatitis B in the territory of the Russian Federation during the past five years. The reduction of viral hepatitis B incidence was achieved thanks to a higher vaccination coverage of both children and adults. The article presents an overview of monovalent and combination recombinant hepatitis B vaccines licensed in the Russian Federation. It describes the WHO position on preventive vaccination against viral hepatitis B, and pays special attention to vaccination of people at risk. The article considers promising areas for improving immunobiological products for hepatitis B prevention, including new technologies used in vaccine production, development and introduction of new adjuvants or adjuvants systems, and development of therapeutic vaccines.